2019
DOI: 10.1093/cercor/bhz291
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Differences in Interneuron Invasion of Neocortex and Piriform Cortex during Mouse Cortical Development

Abstract: Establishing a balance between excitation and inhibition is critical for brain functions. However, how inhibitory interneurons (INs) generated in the ventral telencephalon integrate with the excitatory neurons generated in the dorsal telencephalon remains elusive. Previous studies showed that INs migrating tangentially to enter the neocortex (NCx), remain in the migratory stream for days before invading the cortical plate during late corticogenesis. Here we show that in developing mouse cortices, INs in the pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…KCC2 expression during development has been proved to be highly region and species-specific. In the mouse, Hsing and colleagues (Hsing et al 2020) showed that in neocortical areas very low KCC2 expression can be detected at P0, whereas KCC2 signal in the piriform cortex can be detected as early as E15.5. Nonetheless both regions display similar levels of expression by P7.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…KCC2 expression during development has been proved to be highly region and species-specific. In the mouse, Hsing and colleagues (Hsing et al 2020) showed that in neocortical areas very low KCC2 expression can be detected at P0, whereas KCC2 signal in the piriform cortex can be detected as early as E15.5. Nonetheless both regions display similar levels of expression by P7.…”
Section: Discussionmentioning
confidence: 99%
“…KCC2 expression during development has been proved to be highly region and species-specific. In the mouse, Hsing and colleagues (Hsing et al 2020) showed that in neocortical areas very low KCC2 expression preprint (which was not certified by peer review) is the author/funder. All rights reserved.…”
Section: Circuit-specific Kcc2 Deficiency In Mecp2 Ko Micementioning
confidence: 99%
“…Quantitative RT-PCR was performed as described 50 . Briefly, RNA samples were collected from dorsal telencephalon at E13.5 using TriPure Isolation Reagent (Roche).…”
Section: Methodsmentioning
confidence: 99%
“…Cell nuclei were counterstained with DAPI (Vector). Neuronal birthdating analyses were performed as described 50 . Briefly, EdU (500 ng) was injected into timed-pregnant mice, and the EdU-positive cells were detected with a Click-iT EdU imaging kit (Life Technologies).…”
Section: Methodsmentioning
confidence: 99%
“…Cell nuclei were counterstained with DAPI (Vector). Neuronal birthdating analyses were performed as described 44 . Briefly, EdU (500 ng) was injected into timed-pregnant mice, and the EdU-positive cells were detected with a Click-iT EdU imaging kit (Life Technologies).…”
Section: Mouse Linesmentioning
confidence: 99%